Effect of ultrasonic impact treatment on creep characteristics and evolution of Zr1Nb alloy nanostructure - Sokolenko, V.I.; Gorbatenko, V.M.; Karaseva, E.V.; Mats, A.V.; Savchuk, E.S.; Frolov, V.A. (Functional Materials, 2018)
Effect of ultrasonic impact treatment on creep characteristics and evolution of Zr1Nb alloy nanostructure has been studied. Under the ultrasonic impact treatment the level of internal stresses in the nanostructured material decreases due to formation of the more equilibrium boundary structure without appreciable grain growth. Subsequent deformation of the nanostructured Zr1Nb alloy under creep conditions at 700 K induces the relaxation of internal stresses as a consequence of dynamic recrystallization. As a result, the new stable nanostructure is formed that appreciably increases thermomechanical stability of the alloy.